Mobile visualization: a framework to assist decision-making in financial management - Mohammad Fadhli Asli (2017)
Nowadays, every organization has their own management process, and equipped with information systems to assist them. With the continuous data generation from the system, it is overwhelming for the users to make use of all this information in their process of decision-making. Information visualizations offered the advantageous data exploration by visualizing the relevant information for the user to retrieve and understand promptly. However, only few researches were found regarding information visualization in mobile platform especially in context of decision-making process for financial management. This research developed a framework through the uses of mobile visualization as a concept tool to assist the decision-making in financial management. An action case research strategy, including observation and interview were used to procure results for analysis and to answer the research questions and final conclusion. The latest statistics presented by technology observant such as Morgan Stanley Research have proven the increase of mobile application usage and development that led the research to perceive that mobile visualization will be used in the future context.